Non-heat related impacts of climate change on working populations - Charmian M. Bennett; Anthony J. McMichael (Taylor & Francis Group, 2010)
Environmental and social changes associated with climate change are likely to have impacts on the well-being, health, and productivity of many working populations across the globe. The ramifications of climate change for working populations are not restricted to increases in heat exposure. Other significant risks to worker health (including physical hazards from extreme weather events, infectious diseases, under-nutrition, and mental stresses) may be amplified by future climate change, and these may have substantial impacts at all scales of economic activity. Some of these risks are difficult to quantify, but pose a substantial threat to the viability and sustainability of some working populations. These impacts may occur in both developed and developing countries, although the latter category is likely to bear the heaviest burden.This paper explores some of the likely, non-heat-related health issues that climate change will have on working populations around the globe, now and in the future. These include exposures to various infectious diseases (vector-borne, zoonotic, and person-to-person), extreme weather events, stress and mental health issues, and malnutrition.